(untitled) (Marketing Journal, 2025)
The article analyzes the renewal of local governance within the context of a transformational economy, with a focus on Urgench cityʼs emerging digital management model. Technological practices such as online citizen feedback, resource monitoring, and neigh borhood -level control are explored. A comparative analysis with international cases highlights the practical and theoretical potential of the Urgench experience. The study concludes with evidence -based policy recommendations.